2022
DOI: 10.1002/jso.26851
|View full text |Cite
|
Sign up to set email alerts
|

The future of endoscopic resection for early gastric cancer

Abstract: Endoscopic resection for early gastric cancer is recommended when the risk of lymph node metastasis is negligible and should be performed through submucosal dissection due to well‐established short‐ and long‐term results. To overcome technical difficulties and decrease adverse events some techniques have been studied. This review outlines current strategies for improving patient selection and highlights innovative techniques that help minimize adverse events. Moreover, we discuss how to improve management afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
(173 reference statements)
0
3
0
Order By: Relevance
“…Preoperative evaluation of LNM in gastric cancer is still lacking of effective means. It is of great clinical significance to understand the characteristics and rules of LNM in EGC 16–18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative evaluation of LNM in gastric cancer is still lacking of effective means. It is of great clinical significance to understand the characteristics and rules of LNM in EGC 16–18 …”
Section: Discussionmentioning
confidence: 99%
“…It is of great clinical significance to understand the characteristics and rules of LNM in EGC. [16][17][18] In this study, risk factors of LNM in EDGC cases were identified. As analysis results showed, preoperative hypoalbuminemia, significant preoperative weight loss, tumor diameter, location, and number, histological classification, tumor infiltration depth, and vascular infiltration tended to be associated with LNM.…”
Section: Discussionmentioning
confidence: 99%
“…It generated a variety of images. The evaluation methods and the variables were different during a single moment [45]. Moreover, physicians and pathologists will be able to use CNN's findings as a determining the diagnosis of challenging cases.…”
Section: Researchersstudies and Articles Were Publishedmentioning
confidence: 99%